Qualidade do sêmen bovino criopreservado em diferentes concentrações espermáticas - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The quality of bovine semen is very important in achieving good pregnancy percentages, as the use of poor semen can harm the results of the artificial insemination program, thus losing all the efforts made in the preparation of the herd and investments in technology. There are few studies in the literature that specifically explore the relationship between the quality of the seminal samples of the bulls and the ideal concentration of viable spermatozoa inseminated and their influence on fertility. The objective was to evaluate the effect of sperm concentration on sperm kinetics and morphology of cryopreserved bovine semen at different sperm concentrations. The concentrations of sperm evaluated were 10x106 , 20x106 , 30x106 , 40x106 and 50x106 spermatozoa per vial of the same ejaculate. The thawed doses for analysis had their spermatozoa submitted to CASA tests of kinetics and sperm morphology, slow thermoresistance test (TTR/L) and fast thermoresistance (TTR/R) test. Statistical analysis was performed using the SISVAR® program p<0,05 and the Tukey test and the Correlation test were used. The spermatic concentrations of 30x106 and 40x106 of spermatozoa per vane were those that presented better spermatic quality.
Keywords: CASA; Dose inseminante; Termorresistência; Touros; Bulls; CASA; Dose inseminate; Thermoresistance; CIENCIAS AGRARIAS